Obstructive Sleep Apnea in patients with Cystic Fibrosis and non-Cystic Fibrosis Bronchiectasis and its relation with clinical parameters - VEZİR, DUYGU; KOCAKAYA, DERYA; CEYHAN, BERRİN (My University, 2022)
Objective: This study was designed to assess obstructive sleep apnea (OSA) in adult patients with cystic fibrosis (CF) and non-CF bronchiectasis (BE) and to relate it with clinical characters. Methods: 35 CF (27yrs) and 35 non-CF (24yrs) BE patients were included. Demographic characteristics, medications, comorbidities, BMI, dyspnea scales, pulmonary functions, sputum cultures, exacerbations, and hospitalizations were recorded. Epworth Sleepiness Scale (ESS) questionnaire was filled and polysomnography was performed for each patient. Results: ESS scores did not show any significant difference between CF and non-CF BE patients. 37 (53%) of all patients had OSA. There was no significant difference for OSA risk between CF and non-CF BE patients (54% vs 51%, respectively). Male gender was found to be a risk factor for OSA (68% of males vs 41% of females, respectively, p:0.026). Total sleep time, sleep efficiency, sleep latency, time spent awake after falling asleep, ODI, AHI, AHI in supine position and REM phase did not show any significant difference between CF and non-CF patients. CF patients had significantly lower mean oxygen saturation (p:0.001) and lowest oxygen saturation (p:0.0024) levels and higher heart rate (p:0.02) compared to non-CF BE patients. Multiple logistic regression analysis of all patients revealed male gender and disease duration as risk factors for OSA (p:0.023 and p:0.041 respectively).
Keywords: Tıp; Dahili Tıp Bilimleri; Göğüs Hastalıkları ve Allerji; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Chest Diseases and Allergy; Health Sciences; SOLUNUM SİSTEMİ; Klinik Tıp; Klinik Tıp (MED); RESPIRATORY SYSTEM; CLINICAL MEDICINE; Clinical Medicine (MED); Solunum Bakımı; Akciğer ve Solunum Tıbbı; Respiratory Care; Pulmonary and Respiratory Medicine; Apnoea / Hypopnea; Adults; Orphan diseases